Credit Services and Financial Performance of Selected Small and Medium Enterprise in Mbale City: A Case of Industrial Division - Nabuduwa Zaifah (Uganda Christian University, 2024)
This study investigated the impact of credit services on the financial performance of small and medium-sized enterprises (SMEs) in Industrial City Division, Mbale City, guided by three objectives. A case study research design was used. The study predominantly employed a quantitative approach but also used a qualitative approach. The study population consisted of 80 participants. A sample size of 66 respondents was selected using simple and purposive sampling techniques. Firstly, long term loans were found to explain 4.3% of the variance in SMEs' financial performance, predominantly benefiting medium-sized enterprises for business expansion with manageable repayment schedules (Bayene, 2002). Secondly, short term loans showed minimal impact (1.1%), often burdened by stringent repayment terms unsuitable for SMEs' cash flow cycles (Gibson, 2004). Additionally, trade credit emerged as significant, explaining 13.0% of the variance by supporting continuous product supply and operational flexibility (Kakuru, 2001). In conclusion, long term loans are advantageous for sustained growth in medium-sized enterprises, whereas short term loans may not significantly enhance financial performance due to their restrictive terms. Recommendations include tailored financial training for effective long term loan utilization and promotion of trade credit adoption to optimize SMEs' business operations and financial performance in the region, contributing to broader economic development goals.